2011
DOI: 10.1007/s11409-011-9069-5
|View full text |Cite
|
Sign up to set email alerts
|

Applying learning strategy questionnaires: problems and possibilities

Abstract: This article discusses measuring learning strategies by means of questionnaires. In 'multi-method' research, in which think-aloud measures are compared with questionnaires, low or moderate correlations are found. A conclusion often drawn is that learners are not able to verbally report on their learning activities. Alternative explanations concern two other possibilities: first, that different learning strategies may be measured by the two methods; second, that the measuring methods may be aimed at different l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 40 publications
(57 reference statements)
0
72
0
Order By: Relevance
“…As discussed in the theoretical framework, this problem is likely to be caused by memory distortions as well as by variation in interpretation of the questions (McNamara 2011;Veenman 2011b). It could be that such issues can be addressed by fitting the formulation of the items more closely to the learning task (Schellings 2011). However, in our study we found that fitting the formulation of the questions to the learning domain (in this case by adding the word mathematics) does not seem to make the statements specific enough.…”
Section: Conclusion and Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…As discussed in the theoretical framework, this problem is likely to be caused by memory distortions as well as by variation in interpretation of the questions (McNamara 2011;Veenman 2011b). It could be that such issues can be addressed by fitting the formulation of the items more closely to the learning task (Schellings 2011). However, in our study we found that fitting the formulation of the questions to the learning domain (in this case by adding the word mathematics) does not seem to make the statements specific enough.…”
Section: Conclusion and Discussionmentioning
confidence: 58%
“…Firstly, the fact that self-report questionnaires are collected separate from the learning task means that students have to retrieve earlier processes and performance from their long term memory. Self-report questionnaires thus are susceptible to memory distortion issues (McNamara 2011;Schellings 2011;Veenman 2011b). Secondly, students can differ in their frame of reference as to which situations they have in mind when answering the questions and interpreting the scales (McNamara 2011;Schellings 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…5 That they work is generally agreed upon. See Wilson and Bai (2010). specific, but what cannot be disputed is that there is an overabundance of them (Schellings, 2011). Case in point, Block (1986) touts the success rate of "integrators" versus "non-integrators," Oxford (1990) presents us with a kaleidoscope of learning strategies that she organizes into six different groups: cognitive, metacognitive, memory-related, compensatory, affective, and social.…”
Section: The Primary Elements Behind Descriptive Researchmentioning
confidence: 99%